Evolution of COQ-Synthome Transcripts and CoQ Levels in Mice Tissues Along Aging: Effect of Resveratrol and Exercise - Meza-Torres, Catherine; Reyes-Torres, Iván; Bui Thanh, Tung; Campos-Silva, Carmen; Rodriguez-Bies, Elisabet; Navas, Plácido; López-Lluch, Guillermo (Antioxidants, 2025)
The balanced control of the synthesis of CoQ along the life of the organism is essential to maintain the respiratory capacity at the mitochondria and the antioxidant protection of cell membranes and plasma lipoproteins. For this reason, we determined the levels of the transcripts of the CoQ-synthome along the life of mice in comparison with the levels of antioxidant enzymes and the levels of CoQ in these animals. Surprisingly, we found that some organs such as liver, kidney and heart show great differences in mRNA levels of some COQ-genes along life whereas others such as the brain or gastrocnemius muscle do not show differences. Interestingly, these differences were not related to the total amount of CoQ in these tissues, indicating a discrepancy between the transcript activity of the CoQ-synthome and the level of the product, CoQ. This likely responds to different regulatory levels including mRNA lifespan and CoQ turnover. Further, resveratrol and physical activity in old animals can modulate some transcripts but many of them are in an organ-dependent effect, indicating a different response to the regulators.